Analyzing rowing crews in different rowing boats based on angular velocity measurements with gyroscopes - Gravenhorst, F.; Tessendorf, B.; Arnrich, B.; Codoni, C.; Tröster, G. (Proceedings of the International Symposium on Computer Science in Sport (IACSS 2011), 2011)
The overall performance in rowing competitions depends on crew-based parameters like technique and physical strength, environmental conditions like water temperature and wind, and material like the shape and the settings of the rowing boat. The market offers a broad variety of rowing boats. However, there is still no standardized test procedure which enables an objective comparison of different rowing boats and boat settings for a given crew. In this work we are proposing three performance metrics which can be used to compare the fitness of different boats, i.e. its stability in a quantitative way. The metrics are based on angular velocity measurements which can be obtained by gyroscopes, which usually come as a part of inertial measurement units (IMUs). In collaboration with national rowing team coaches we equipped two rowing boats of world level athletes with miniaturized IMUs. Based on the collected data we benchmarked the boats in respect of their stability for the given crew.